2014
DOI: 10.25138/8.2.a.11
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Confucian Values on Modern Hierarchies and Social Communication in China and Korea: A Comparative Outline

Abstract: Confucianism and Neo-Confucianism, being by-products of socio-political and educational developments at various stages of Chinese history, have permeated to a varying degree several aspects of life in East Asian societies. China itself, along with its neighbouring states-such as Vietnam and Korea-despite political changes, globalization, and adoption of non-traditional systems of governance, have retained hierarchic models of communication derived from NeoConfucianism. The nature of the doctrine and the transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Familism, as an important part of Confucianism, has a great influence on Chinese teachers ( Sleziak, 2014 ). Confucian familism is a strong belief that emphasizes the centrality of the family unit and stresses that people ought to work hard to provide support to family members ( Yang, 2004 ).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…Familism, as an important part of Confucianism, has a great influence on Chinese teachers ( Sleziak, 2014 ). Confucian familism is a strong belief that emphasizes the centrality of the family unit and stresses that people ought to work hard to provide support to family members ( Yang, 2004 ).…”
Section: Literature and Hypothesesmentioning
confidence: 99%
“…First, different cultural perspectives of other East Asian countries on Para-sport activism should be considered. Some research found subtle differences bringing in big impact of Confucianism on social model among East Asian countries (Huang & Chang, 2017;Sleziak, 2014). Second, future research could consider what types of activism disabled athletes prefer to participate in to achieve a better understanding of the multifaceted nature of activism and highlight their potential impact on society.…”
Section: Discussionmentioning
confidence: 99%
“…Confucianism, which dominated Korean culture for over 500 years during the Joseon dynasty between 1392 and 1910, still influences the way of life among Koreans, especially in human relationships. It emphasizes the importance of family and social harmony (Park & Cho, 1995; Sleziak, 2014). The Five Principles on human relationships prescribe specific duties to each of the participants in five sets of relationships: ruler to the ruled; father to sons; husband to wife; elders to youngers; and friends among themselves (M.…”
Section: Interpersonal Relationships and Leadership In South Koreamentioning
confidence: 99%